2022
DOI: 10.1001/jamaneurol.2022.0829
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fenfluramine for the Treatment of Seizures Associated With Lennox-Gastaut Syndrome

Abstract: This randomized clinical trial examines the change from baseline in drop seizure frequency, response rates, and improvement on the Clinical Global Impression scale among patients with Lennox-Gastaut syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 35 publications
5
63
0
Order By: Relevance
“…Of note, FFA has also shown efficacy in reducing seizures in other drugresistant epilepsy syndromes including Lennox-Gastaut syndrome and CDKL5 deficiency disorder. 21,22 As well as reductions in total seizures and GTCSs, we found a statistically significant reduction in seizure days, in line with data from the pivotal RCTs that have reported increases in seizure-free days and statistically significant increases in seizure-free intervals. 6,7 In addition, FFA was associated with improvements in overall condition (physician-rated CGIC).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, FFA has also shown efficacy in reducing seizures in other drugresistant epilepsy syndromes including Lennox-Gastaut syndrome and CDKL5 deficiency disorder. 21,22 As well as reductions in total seizures and GTCSs, we found a statistically significant reduction in seizure days, in line with data from the pivotal RCTs that have reported increases in seizure-free days and statistically significant increases in seizure-free intervals. 6,7 In addition, FFA was associated with improvements in overall condition (physician-rated CGIC).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the ultimate treatment goal of seizure freedom or near freedom from seizures has been observed in a notable proportion of patients in our study (29.5% with ≤1 seizure per month) and others, 6,7,16 with Nabbout et al 7 reporting a statistically significant difference in the proportion of patients having ≤1 convulsive seizure during the 14‐week treatment period with FFA compared to placebo (Table ). Of note, FFA has also shown efficacy in reducing seizures in other drug‐resistant epilepsy syndromes including Lennox–Gastaut syndrome and CDKL5 deficiency disorder 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Most frequent adverse events (at least 10%) included decreased appetite, somnolence, fatigue, vomiting, diarrhea and pyrexia. No cardiovascular complications were reported ( Knupp 2021a ). After completion of the randomized-controlled phase, patients were enrolled in the open-label extension study and received FFA twice daily for up to 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter, double-blind, placebo-controlled RCT was conducted in 263 LGS patients (2–35 years old) with ≥2 drop seizures/week [ 69 ] ( Figure 2 ). The median percentage reduction in frequency of drop seizures was 26.5% ( p < 0.01) with 0.7-mg/kg/d, 14.2% ( p = 0.09) with 0.2-mg/kg/d, and 7.6% in the placebo group during 14 weeks of the treatment period.…”
Section: Clinical Use Of Ffa In Epilepsymentioning
confidence: 99%
“…More patients in the 0.7-mg/kg/d group than in the placebo group had ‘much improved’ or ‘very much improved’ ratings on the Clinical Global Impression of Improvement scale (26% vs. 6%; p =.001). Following completion of the phase 3 RCT, 247 patients enrolled for the open-label extension study [ 70 ]. Interim analysis at one year showed that 83 patients (33.6%) discontinued taking FFA in the interval.…”
Section: Clinical Use Of Ffa In Epilepsymentioning
confidence: 99%